(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It consists of blade tensioning hand wheel which is used to give proper tension to blade. Blade guide arm is used to guide the blade for proper cutting of material. Control panel is used to control movement of blade as well as blade roller. Blade is used to cut the material which is mounted on two band saw rollers which is move away from each other. Quick positioning vice is used to clamp the raw material. Vice hand wheel is used to clamp the work piece as well as it gives feed to work piece. Chip try is used to collect chip which is formed during operation. Coolant level gauge is indicating the level of coolant in coolant tank. A band saw is a power tool which uses a blade consisting of a continuous band of metal with teeth along one edge to cut various work pieces. The band usually rides on two wheels rotating in the same plane, although some band saws may have three or four wheels. Bands awing produces uniform cutting action as a result of an evenly distributed tooth load. Band saws are used for woodworking, metalworking, or for cutting a variety of other materials. They are particularly useful for cutting irregular or curved shapes, but can make straight cuts.